Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.jsat.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The In-Session and Long-Term Role of a Significant Other in Motivational Enhancement Therapy for Alcohol Use Disorders

Abstract: Objective To examine how significant other (SO) language in support of or against client abstinence from alcohol influences clients’ in-session speech and drinking behavior over the 9 months post-Motivational Enhancement Therapy (MET). Method Sequential analyses were used to examine the language of Project MATCH clients who invited an SO to participate in an MET session. Hierarchical regressions investigated the predictive relationship between SO language and clients’ post-treatment drinking behavior. A coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The interplay between IP and SO CT and ST, and the changes in this interplay from the first session to midtreatment, is notable. In both sessions, it appears that SO use of CT has a powerful influence on the IP, as reflected in previous studies of select conjoint treatment sessions from Project MATCH (Apodaca et al, 2013;Bourke et al, 2016;Manuel et al, 2012). However, our study shows that the nature of that influence changes over the course of treatment.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The interplay between IP and SO CT and ST, and the changes in this interplay from the first session to midtreatment, is notable. In both sessions, it appears that SO use of CT has a powerful influence on the IP, as reflected in previous studies of select conjoint treatment sessions from Project MATCH (Apodaca et al, 2013;Bourke et al, 2016;Manuel et al, 2012). However, our study shows that the nature of that influence changes over the course of treatment.…”
Section: Discussionsupporting
confidence: 74%
“…It is reasonable to expect that partners could facilitate change talk by offering encouragement or solutions and, conversely, promote sustain talk by expressing skepticism or blame, disagreeing with the client, or focusing on negative consequences of drinking. Studies that have examined the impact of significant others (SOs) on client speech relied on therapy sessions in which a family member, partner, or friend functioned as an occasional adjunct to individual AUD treatment and a general source of feedback and support (Apodaca, Magill, Longabaugh, Jackson, & Monti, 2013;Bourke, Magill, & Apodaca, 2016;Manuel, Houck, & Moyers, 2012). Manuel and colleagues (2012) found several significant correlations among SO behaviors, client change talk, and drinking outcomes, but they were limited by a small sample size of a subset of sessions from Project MATCH.…”
Section: Change Talk and Sustain Talkmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis [ 30 ], the involvement of a SO in treatment was shown to be associated with a reduction of both substance use and problems related to the substance use. In MI for AUD specifically, the involvement of a SO in treatment can lead to more change talk and better treatment outcomes [ 5 , 31 ]. Despite recommendations of SO involvement in treatment, other studies have also noted that few SOs participate in sessions.…”
Section: Discussionmentioning
confidence: 99%
“…For years, MI was conducted only in a traditional one-on-one (interventionist to client) format. However, increasingly research has shown that MI lends itself well to a dyadic format, with two people who know one another (e.g., peers, co-workers, friends, romantic partners), as it is within this kind of relationship that people can most successfully work together toward behavior change (Bourke et al, 2016; D’Amico et al, 2017; Miller & Rose, 2010; Monti et al, 2014). Importantly, a peer-based MI can use the responsibility and relationship of friends as a framework to foster collaborative efforts to increase readiness and decrease barriers to helping behavior.…”
mentioning
confidence: 99%